2005
DOI: 10.1515/cclm.2005.048
|View full text |Cite
|
Sign up to set email alerts
|

Butyrylcholinesterase activity and metabolic syndrome in obese patients

Abstract: Total butyrylcholinesterase activity (EC 3.1.1.8) was previously suggested as a marker for metabolic syndrome. The present study examined total butyrylcholinesterase activity and the relative and absolute activities of two butyrylcholinesterase electrophoretic bands (C(4/5) and C(OF) in 99 obese individuals (body mass index > or = 30 kg/m2) presenting the CHE2 C5- phenotype of the CHE2 gene. Anthropometric, hormonal and biochemical variables already associated with metabolic syndrome were also examined. The da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 22 publications
4
22
0
2
Order By: Relevance
“…The BuChE was related to some general characteristics such as BMI and sex. The BuChE of men (9557.0 U/L) was significant higher than women (8143.0 U/L) workers (Independent sample t-test, p \ 0.01) which supported previous studies [10][11][12]. There was no significant correlation, in either men or women, with alcohol intake or smoking.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The BuChE was related to some general characteristics such as BMI and sex. The BuChE of men (9557.0 U/L) was significant higher than women (8143.0 U/L) workers (Independent sample t-test, p \ 0.01) which supported previous studies [10][11][12]. There was no significant correlation, in either men or women, with alcohol intake or smoking.…”
Section: Discussionsupporting
confidence: 86%
“…Venkata et al [18] found that pseudo-cholinesterase concentration decreased correspondingly and specifically with more functional liver cell damage. Other studies [19,20] found that plasma cholinesterase had relationship with triglycerides, HDL-C, and LDL-C. More recent reports [10,11,21,22] extended the association to wide range of variables with the metabolic syndrome including body mass index, apolipoprotein concentrations, insulin, liver enzymes, and blood pressure. Moreover, Nyblom et al [23] reported that the SGOT/ SGPT ratio can be used as an indicator of cirrhosis in alcoholic liver disease, hepatitis C and supported that the high ratio ([1.1) actually reflects cirrhotic changes in the liver.…”
Section: Discussionmentioning
confidence: 95%
“…Positive correlations of BMI (4,34) and MS (13) with BChEA, AC 4/5 and AC OF have also been reported.…”
Section: Butyrylcholinesterase and Diabetes Mellitusmentioning
confidence: 77%
“…In light of some of these correlations, Kutty and cols. (12) proposed the use of BChEA as a complementary risk factor for coronary artery disease (CAD), and also suggested the relationship of BChEA to metabolic syndrome (MS) (13).…”
Section: Introductionmentioning
confidence: 99%
“…BChE has been proposed to be a marker of low-grade systemic inflammation, often seen in insulin resistance syndrome [29]. Although it may not play a causal role, BChE has been suggested to modulate its expression [30], or be a secondary marker [31]. The ability of high serum lipids to induce stereoscopic alteration in its configuration could be a pathogenic mechanism [32].…”
mentioning
confidence: 99%